Studi Korelasi Motivasi Belajar terhadap Hasil Belajar Matematika Selama Daring - Nisa Wijayanti; Sri Adi Widodo (Journal of Instructional Mathematics, 2021)
The purpose of this study was to determine how much the relationship between learning motivation and learning outcomes online mathematics at SMP N 3 Wates. This research includes research with a quantitative approach and the type of research is ex post facto because it does not provide treatment to the research sample and the form of the relationship is a causal relationship. The population in this study were students of SMP N 3 Wates. The sampling technique was using cluster random sampling technique. The data collection techniques used were documentation and a learning motivation questionnaire. This study uses inferential statistical data analysis techniques, with several prerequisite tests. The results of this study indicate that the relationship between learning motivation and online mathematics learning outcomes at SMP N 3 Wates is in a low category.